ANALISIS KELAYAKAN INVESTASI BUDIDAYA TAMBAK UDANG EKTENSIF DAN SEMI INTENSIF (Studi Kasus Budidaya Udang Bapak Abdul Wafi dan Bapak Sakkin di Pulau Bawean) - Khairuddin, Khairuddin; Mujanah, Siti; Murnawan, Hery (TEKNIKA, 2023)
Bawean Island is one of the areas located in Gresik Regency. The main commodities of Bawean Island are agriculture and fisheries. The sector that is the mainstay is fisheries, where the presence of marine is one of the factor sectors that influence the development of the fisheries sector. Shrimp cultivation is an aquaculture business related to the maintenance of shrimp from fry until the shrimp are ready for sale. Shrimp aquaculture systems consist of extensive and semi-intensive systems. Extensive shrimp farming is shrimp ponds that still use nature’s grace and low costs. While semi-intensive shrimp ponds are shrimp ponds that require high costs compared to extensive shrimp ponds. The methods used in this research are Net Present Value (NPV), Internal Rate Of Return (IRR), Payback Period (PP), and Profibility Index (PI) methods. The author conducted a survey by calculating the amount of income and income made in Extensive and Semi-Intensive Shrimp Ponds to find out how well a business is built. The results of the Extensive Shrimp Pond research show an income of Rp. 340,000,000 and semi-intensive Shrimp Ponds with an income of Rp. 671,000,000, NPV of Extensive Shrimp Ponds of Rp. 219,486,340 and Semi Intensive Shrimp Ponds of Rp. 339,274,084, IRR for Extensive Shrimp Ponds of Rp. 6.01% and Semi-Intensive Shrimp Ponds of Rp. 6.82%, PP Shrimp Ponds Extensive 3 months 41 days and PP Shrimp Ponds Extensive 3 months 52 days. PI for Extensive Shrimp Ponds Rp. 4.93 and Rp. Semi-Intensive Shrimp Pond. 9,42.